Anterior Cervical Decompression and Arthrodesis for the Treatment of Cervical Spondylotic Myelopathy. Two to Seventeen-Year Follow-up - EMERY, SANFORD E.; BOHLMAN, HENRY H.; BOLESTA, MICHAEL J.; JONES, PAUL K. (Journal of bone and joint surgery. American volume, 1998)
We reviewed the cases of 108 patients with cervical spondylotic myelopathy who had been managed with anterior decompression and arthrodesis at our institution. Operative treatment consisted of anterior discectomy, partial corpectomy, or subtotal corpectomy at one level or more, followed by placement of autogenous bone graft from the iliac crest or the fibula. At the latest follow-up examination, thirty-eight of the eighty-two patients who had had a preoperative gait abnormality had a normal gait, thirty-three had an improvement in gait, six had no change, four had improvement and later deterioration, and one had a worse gait abnormality. Of the eighty-seven patients who had had a preoperative motor deficit, fifty-four had complete recovery; twenty-six, partial recovery; six, no change; and one had a worse deficit. The average grade according to the system of Nurick improved from 2.4 preoperatively to 1.2 (range, 0.0 to 5.0) postoperatively. A pseudarthrosis developed in sixteen patients, thirteen of whom had had a multilevel discectomy. Only one of thirty-eight arthrodeses that had been performed with use of a fibular strut graft was followed by a non-union. An unsatisfactory outcome with respect to pain was significantly associated with pseudarthrosis (p < 0.001). The development of complications other than non-union was associated with a history of one previous operative procedure or more (p = 0.005). Recurrent myelopathy was rare, but when it occurred it was associated with a pseudarthrosis or stenosis at a new level. The strongest predictive factor for recovery from myelopathy was the severity of the myelopathy before the operative intervention—that is, better preoperative neurological function was associated with a better neurological outcome. Anterior decompression and arthrodesis with autogenous bone-grafting can be performed safely, and is associated with a high rate of neurological recovery, functional improvement, and pain relief, in patients who have cervical spondylotic myelopathy.